Synthesis of Nanomaterials and their Integration in Wastewater Treatment Processes - Azhar, Muhammad Rizwan (Curtin University, 2018)
Metal organic frameworks (MOFs) are new class of nanomaterials possessing high surface area, large volume and tuneable pore size. These unique materials are promising candidates for wastewater treatment. In this work, several water stable MOFs, namely HKUST-1, UiO-66, ZIF-67, BioMOF-11, MIL-96 and their derivatives, were synthesized solvo/hydrothermally and used in adsorption and/or catalytic degradation of antibiotics, dyes, and personal care products. It is demonstrated that the materials exhibited high adsorption capacity and good catalytic performance.